Lithium defects and diffusivity in forsterite - Zhang, Feiwu; Wright, Kathleen (Pergamon-Elsevier Science Ltd, 2012)
Lithium is an important geochemical tracer used to infer the thermal and chemical evolution of minerals in the Earth’s upper mantle. Knowledge of point defect chemistry and diffusion is critical for the interpretation of Li distribution in minerals. Using quantum mechanical methods we show that in forsterite Li will be incorporated as bound interstitial–substitutional pairs. Furthermore, there will be temperature dependent fractionation of its two isotopes between the different sites. The fractionation decreases dramatically from 87.1& at 300 K to 1.0& at 3000 K. Diffusion is predicted to occur via twointer-related mechanisms: Mg–Li exchange, and a second, vacancy assisted interstitial mechanism. This behaviour is complex, facilitates migration of the heavier isotope and offers insights into observations of Li mobility and zoning in olivine, the most volumetrically important upper mantle mineral.